The Outcomes of Sub Inguinal Varicocelectomy on Seminal Fluid Analysis Parameters in Infertile Patients with Clinically Diagnosed Varicoceles - Sabah Kadhim Alkaabi, Ammar; Abdulameer Abod, Salam; Maki Mohammed Abualsud, Afrah (American Journal of Biomedicine and Pharmacy, 2026)
Background; a comparison study in seminal fluid parameters (count, motility and morphology) pre and post subinguinal varicocelectomy, in patients with history of primary infertility, normal sperm count and clinically diagnosed varicocele. Patients and method; in this study one hundred infertile patients had primary infertility (1-7 years), normal sperm density and clinical confirmed varicocele were included. A seminal fluid analysis has been recorded preoperative and sex months post varicocelectomy. Results; 100 patients included in this study; mean age was 22.43± 7.24. Mean period of infertility was 2.5 years (ranging from 2-7 years), a significant changing in motility has been noted postoperative in normal sperm count patients. Conclusion; in patients with primary infertility, varicocele and normal sperm count preoperatively there was significant improvement in sperm motility post varicocelectomy while no postoperative significant improvement in sperm morphology for those patients.